ASPEK HUKUM BAGI PENYEBAR HOAX TENTANG ADANYA WABAH PENYAKIT DIFTERI DI SURAKARTA - Nurcahya, Doni Kaseh; Hapsari, Sephia Tyas; Ambarwati, Silvia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In the development of the technology there are good and bad impacts such as the spread of false news or information that is spread in indonesian society. For hoax spread, article 28 paragraph 1 of ITE law is threatened and article 45A paragraph (1) of law 19/2016 is threatened with a maximum imprisonment of 6 (six) years and/or a maximum fine of Rp 1 billion. This research is descriptive in nature wich illustrates the problem under study by describing it coherently. The type of research data is secondary data from other sources. Using data collection techniques with library research and qualitative analysis techniques. This study analyzes the legal aspects of  hoax information in indonesia